Step-by-step explanation:
Let the numbers be x and y
2 consecutive even nos.
therefore y = x+2
twice of the first (2x) is 46 more than y
2x = y+46
Solving both the equations
x - y + 2 = 0
(-)2x - y - 46 = 0
____________
-x + 0 + 48 = 0
____________
x = 48
y = x+2
= 48 +2
= 50
Therefore the 2 nos. are 48 and 50
Hope this answers helps you
Answer:
x = (22/17), y= (79/17)
Step-by-step explanation:
Just substitute x = 2y - 8 into y = 9x - 7 and solve.
<span>The normal curve is described by a bell curved graph. The bell curved graph of a normal distribution depends on two factors: the mean and the standard deviation. The mean identifies the position of the center and the standard deviation determines the height and width of the bell.
Therefore, the factor that the width of the peak of the normal curve depends on is the standard deviation.</span>
Answer:
Any negative number would be a counterexample.
Step-by-step explanation:
Since negative numbers get smaller as you multiply them by a larger number, this would prove this conjecture false.